UJI VALIDITAS DAN RELIABILITAS INSTRUMEN PENELITIAN KUANTITATIF - Yusup, Febrinawati (Universitas Islam Negeri Antasari Banajarmasin, 2018)
The research instrument is a tool used to collect data or measure objects of a research variable. To obtain the correct data for the conclusion that is in accordance with the actual situation, then required a valid instrument and consistent and appropriate in providing data of research result. Instrument reliability tests to include test-retest, equivalent, and internal consistency. Internal consistency tests have several testing techniques depending on the type of instrument. Testing techniques included split half test, KR 20, KR 21, and Alfa Cronbach. The value of the validity and reliability of an instrument is influenced by the measured subject, the instrument user, and the instrument itself. Sehinggga, validity and reliability must always be tested before the instrument is used.